Crystal growth and structural remarks on malonate-based lanthanide coordination polymers. Issue 40 (28th September 2016) - Delgado, Fernando S.; Lorenzo-Luís, Pablo; Pasán, Jorge; Cañadillas-Delgado, Laura; Fabelo, Oscar; Hernández-Molina, María; Lozano-Gorrín, Antonio D.; Lloret, Francesc; Julve, Miguel; Ruiz-Pérez, Catalina
Abstract : The synthesis, structural and thermal studies of several malonate-containing lanthanide(iii ) complexes plus a structural overview of twenty-three known homometallic Ln(iii )-malonate systems are provided herein. Abstract : The synthesis, structural characterization and thermal study of new coordination polymers (CPs) of formula [Ln2 (mal)3 (H2 O)5 ]·2H2 O [Ln = Ho (1 ·2H 2 O ), Tb (1a ), Dy (1b ), Er (1c ) and Yb (1d ); mal = malonate], [Ln2 (mal)3 (H2 O)6 ] [Ln = Sm (2 ) and Ce (2a )], [Ce2 (mal)3 (H2 O)6 ]·2H2 O (3 ·2H 2 O ) and [Ce2 (mal)3 (H2 O)3 ]·2H2 O (4 ·2H 2 O ) are presented. Complexes1–4 have been also characterized by single crystal X-ray diffraction. The structure of2 was previously reported (Elsegood, M. R. J., Husain, S., Private Communication, 2014) and it is very close to that of3 . In the light of these results and those previously reported in the literature for malonate-containing lanthanide(iii ) complexes, a detailed overview on the crystal structures and topologies of these systems is provided herein, covering CPs in one, two and three dimensions, as well as the molecular architectures assembled by hydrogen bonding from low-dimensional entities to higher-dimensional supramolecular architectures.